Consideration on English Learning for Undergraduate Students Using a Portable Game Device - Hiromi Ban (New Visions in Science and Technology Vol. 5, 2021)
The Nintendo DS handheld game console, which was developed by Nintendo and has been sold worldwide since 2004, incorporates dual touch screens, voice-recognition features and innovative controls. It has been used not only as a video game device but also as an education tool in the field of education. In this study, a research regarding Nintendo DS software for learning English is conducted with the objective of exploring the possibility of introducing and utilizing the game device as an education tool for undergraduate students. The result is that not only the students who are proficient in English, but also the students who are not and initially displayed a little interest in learning English using the Nintendo DS, they felt it is fun and helpful to work with after actually using it. In addition, it became clear that whether or not the software is suitable for the student affects the continuity of learning.